Utilization of Asmuth-Bloom Algorithm In Data Security Using Secret Sharing Protocol - Heri Santoso; Aidil Halim Lubis; Ali Darta (IJISTECH (International Journal of Information System and Technology), 2021)
Conventional cryptographic algorithms cannot be applied to solve a plaintext (message) into several ciphertexts because conventional cryptographic algorithms can only produce a ciphertext from a plaintext (message). In this case, a cryptographic protocol can be applied, namely the Asmuth-Bloom secret sharing protocol. The methodology used to analyze and design application software and learning the Asmuth-Bloom secret sharing protocol is the Waterfall method. This research is intended to produce a learning software that is able to display the working process of the Asmuth-Bloom secret sharing protocol and the application of the Asmuth-Bloom secret sharing protocol. The working procedure described by the software includes the key formation process, the shadow formation process and the shadow merge process. The software also provides an interface to do the process of splitting a text file into n shadow files and merging m shadow files into the original text file. In addition, the software also provides basic theories related to the two cryptographic protocols and reports the results of the calculation process are stored in a text file with *.txt extension